The Economics of Political Participation and Religion in the Czech Republic - Svatoš, Jiří; Chalupníček, Pavel; Mičúch, Marek, 1980-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2011)
The thesis combines previous economic theory of information, Putnam's theory of correlation between "associational life" and politics and economic theory of differences between churches and sects. This combination provides new point of view on dependence between political participation and religion derived from economic theory. The theory is applied on Czech data, concretely the data from the International Social Survey Program (ISSP) 1998 on Religion. The results are consistent with theory and show that sectarianism has negative effect on political participation with the exception of voting. However, the indirect effect of sectarianism (through "associational life") is also found.
Vedoucí práce: Pavel Chalupníček
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2011
Rok obhajoby 2011
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses